1994
DOI: 10.11150/kansenshogakuzasshi1970.68.403
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abscess due to Pasteurella multocida

Abstract: The patient was a 26-year-old man who complained of headache and vomiting. On examination, there was nothing abnormal, but the edge of the right optic papilla was not clear. His temperature was 38.5 degrees C, pulse 96/min, blood pressure 120/80 mmHg. A space-occupying lesion in his fronto-dextra cupular part was found by CT scanning. He had a 12-year history of chronic purulent otitis. The diagnosis was a brain abscess in the fronto-dextra cupular part. The brain abscess was extracted and Pasteurella multocid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…[1,2] Brugnatelli in his study have reported the first human case of Pasteurella infection causing puerperal sepsis in 1913. [1,2] P. multocida is the most frequent human pathogen. Most infections arise from animal bites or scratches and remain localized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1,2] Brugnatelli in his study have reported the first human case of Pasteurella infection causing puerperal sepsis in 1913. [1,2] P. multocida is the most frequent human pathogen. Most infections arise from animal bites or scratches and remain localized.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is a common cause of infections in animals and rarely causes infections in humans. [1][2][3] The first Pasteurella species was isolated in 1878 by Pasteur in fowl cholera. [1,2] Brugnatelli in his study have reported the first human case of Pasteurella infection causing puerperal sepsis in 1913.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Brugnatelli in his study have reported the first human case of Pasteurella infection causing puerperal sepsis in 1913. [12]…”
Section: Discussionmentioning
confidence: 99%